Digestion and nutrition [electronic resource] - Sullivan, Robert J. [ (Robert James)] (Human body: how it works, 2009)
Learn how the body's digestive system breaks down food, extracts the nutrients the body needs to grow, function, and repair itself, and gets rid of waste materials